2021
DOI: 10.1186/s13053-021-00191-0
|View full text |Cite
|
Sign up to set email alerts
|

Population or family history based BRCA gene tests of breast cancer? A systematic review of economic evaluations

Abstract: Background Nearly 56% of at-risk carriers are not identified and missed as a result of the current family-history (FH) screening for genetic testing. The present study aims to review the economic evaluation studies on BRCA genetic testing strategies for screening and early detection of breast cancer. Methods This systematic literature review is conducted within the Cochrane Library, PubMed, Scopus, Web of Science, ProQuest, and EMBASE databases. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 32 publications
1
6
1
Order By: Relevance
“…The evidence compiled in our review further reinforces the cost-effectiveness of genetic testing in LMICs by incorporating more recent studies published after 2020. Our findings aligned with those reviewed by D’Andrea et al [ 26 ] and Meshkani et al [ 28 ] in highlighting the significance of genetic testing prices as a crucial factor in determining the cost-effectiveness of BC genetic testing especially in Lower MICs such as India [ 37 ]. While our included studies mainly analyze women aged over 30 years [ 37 , 39 , 40 ], it is worth noting that the review summarized by Koldehoff et al [ 27 ] found that most of the included studies focused on women aged 40 years as the preferred age group.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The evidence compiled in our review further reinforces the cost-effectiveness of genetic testing in LMICs by incorporating more recent studies published after 2020. Our findings aligned with those reviewed by D’Andrea et al [ 26 ] and Meshkani et al [ 28 ] in highlighting the significance of genetic testing prices as a crucial factor in determining the cost-effectiveness of BC genetic testing especially in Lower MICs such as India [ 37 ]. While our included studies mainly analyze women aged over 30 years [ 37 , 39 , 40 ], it is worth noting that the review summarized by Koldehoff et al [ 27 ] found that most of the included studies focused on women aged 40 years as the preferred age group.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast to the systematic reviews conducted by D’Andrea et al [ 26 ] and Koldehoff et al [ 27 ], our study encompasses a broader range of genetic testing strategies for BC, including but not limited to BRCA testing, population-based screening, and included those studies without cascade testing. Moreover, we have included the additional three studies from LMICs compared to the previous review by Meshkani et al [ 28 ], who did not impose geographical restrictions on their study selection. The evidence compiled in our review further reinforces the cost-effectiveness of genetic testing in LMICs by incorporating more recent studies published after 2020.…”
Section: Discussionmentioning
confidence: 99%
“…Both showed that PS for founder variants was highly cost-effective. Meshkani [ 68 ] reviews twelve studies on BRCA testing in the general population. An additional study by Manchanda [ 59 ] compared PS to IFH, in multiple countries, and found that PS was not cost-effective in low-middle income countries, especially with low BRCA prevalence, but that PS was cost-effective in middle-high and high income countries It was recommended to further study cost-effectiveness.…”
Section: Discussionmentioning
confidence: 99%
“…A literature search was conducted in MEDLINE (via PUBMED) on 21 September 2022 and the Centre for Reviews and Dissemination (CRD) database to search for health economic modeling studies that addressed women who were offered RRM and/or RRSO after screening for germline BRCA mutations. In addition, we screened the studies included in the most recent systematic reviews published on the topic [ 7 , 11 , 12 , 13 , 14 ]. The search strategy is provided in the Supplementary Materials (File S1) .…”
Section: Methodsmentioning
confidence: 99%